Knowledge, preventive behaviors and risk perception of the COVID-19 pandemic: A cross-sectional study in Turkish health care workers. - Tufan Arslanca; Cihan Fidan; Mine Daggez; Polat Dursun (PLoS ONE)
The coronavirus disease 2019 (COVID-19) outbreak spread to over 100 countries with a total of 100,000 cases during the first week of March 2020. Health care workers, as those on the frontline of the COVID-19 pandemic, are more susceptible to infection. Inadequate related knowledge and preventive behaviors among health care workers might lead to delayed treatment and result in the rapid spread of the infection. Therefore, this study evaluated the knowledge of health care workers with regard to COVID-19. A cross-sectional study was conducted from June 10-18, 2020. Participants were general practitioners, specialists, and nurses working at the forefront of the pandemic. Their knowledge, preventive behaviors, and risk perceptions concerning COVID-19 were evaluated using an online questionnaire created by our medical specialists. The questionnaire consisted of 29, 5, and 4 items about COVID-19 knowledge, preventive behaviors, and risk perceptions, respectively. A total of 251 health care workers completed the questionnaire. The mean age of the participants was 33.88±8.72 years old, and the sample consisted of 68 males (27.08%) and 183 females (72.91%). While there was no difference between the percentage of correct answers given by female and male participants to knowledge-based questions (p>0.05), the percentage of correct answers to the questions on preventive behaviors was significantly higher in female participants than in males (p<0.001). The overall average percentages of correct responses were 91.66% for knowledge-based questions and 85.96% for preventive behavior questions. The scores for knowledge-based questions were higher for medical specialists, whereas nurses scored higher on preventive behavior questions. Government hospital staff showed a significant difference in preventive behaviors compared to that of university hospitals (p<0.05). In addition, there was a positive correlation between knowledge scores and preventive behaviors. Although all the participants (100%) knew that contracting COVID-19 can lead to death, only 66.93% of them were willing to get vaccinated themselves. The knowledge level of health care workers concerning COVID-19 was above 90%, but the level of competence in terms of preventive behaviors was found to be low, especially in males.